Lung Transplantation in Idiopathic Pulmonary Fibrosis - Rosalía Laporta Hernandez; Myriam Aguilar Perez; María Teresa Lázaro Carrasco; Piedad Ussetti Gil (Medical Sciences, 2018)
Despite the advances in recent years in the treatment of idiopathic pulmonary fibrosis (IPF), it continues to be a progressive disease with poor prognosis. In selected patients, lung transplantation may be a treatment option, with optimal results in survival and quality of life. Currently, pulmonary fibrosis is the main cause of lung transplantation. However, mortality on the waiting list of these patients is high, since many patients are referred to the transplant units with advanced disease. There is not a parameter that can predict the survival of a specific patient. Different variables are to be considered in order to decide the right time to send them to a transplant unit. It is also very difficult to decide when to include these patients on the waiting list. Every patient diagnosed with IPF, without contraindications for surgery, should be referred early to a transplant unit for assessment. A uni or bilateral transplantation will be decided based on the characteristics of the patient and the experience of each center. The post-transplant survival of recipients with IPF is lower than that observed in other diseases, such as cystic fibrosis or chronic obstructive pulmonary disease as a consequence of their older age and the frequent presence of associated comorbidity. Post-transplant follow-up must be tight in order to assure optimal level of immunosuppressive treatment, detect complications associated with it, and avoid graft rejection. The main cause of long-term mortality is late graft dysfunction as a consequence of chronic rejection. Other complications, such as infections and tumors, must be considered.